RISK FACTOR ANALYSIS OF PREDIABETES COLLAGE STUDENTS AT THE UNIVERSITAS PENDIDIKAN INDONESIA - Muhamad Jehan Ramadhan; Widya Astuti; Delita Septia Rosdiana; Isti Kumalasari (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Prediabetes is a condition in which blood plasma glucose levels are higher than normal, but still lower than diabetes mellitus levels. This study aimed to determine the factors influencing the occurrence of prediabetes among students at the Indonesia University of Education. The research used a case-control design with a quantitative approach, involving 82 participants selected through purposive sampling, consisting of 41 individuals in the case group and 41 in the control group. Data were obtained through interviews using a structured questionnaire for respondent characteristics and physical activity, SQ-FFQ to assess the consumption pattern of sweet foods and drinks, and measurements of blood glucose levels and nutritional status using a glucometer, weighing scale, and stadiometer. Data analysis was conducted using Chi-Square and logistic regression tests. The habit of consuming sweet foods and beverages showed a significant association with prediabetes (p-value = 0.014), with a six times higher risk of prediabetes. Peer influence had an effect on prediabetes (p-value = 0.021) with a five times higher risk. Physical activity was associated with prediabetes (p-value = 0.045) with a four times higher risk. Nutritional status was associated with prediabetes (p-value = 0.001) with a 26 times higher risk. These findings indicate that the causes of prediabetes among students at the Indonesia University of Education are the habit of consuming sweet foods and drinks, peer influence, physical activity, and nutritional status. Nutritional status is the greatest risk factor causing prediabetes.